The Effect of Using Speed Reading Technique to the Students’ Ability in Comprehending a Text - Martha Florida Sirait; Bertaria Sohnata Hutauruk; Herman (Cetta: Jurnal Ilmu Pendidikan, 2020)
This research aims to determine the effect of applying the effect of speed reading technique on the students’ ability in comprehending a text at grade X of SMA N 4 Pematangsiantar. The problems of this study are “What is the effect of using speed reading technique to the students’ ability in comprehending a text?” and “Is the effect of using speed reading technique more significant to the students’ ability in comprehending a text?” The method used in this research was quantitative research design. The population of this research is the tenth grade students of SMA N 4 Pematangsiantar academic year of 2019/2020. Populations of this research are 235 students. Sample of this research are two classes which are divided into control (X PMIA-6) and experimental class (X PMIA-7). The research instrument in the form of multiple choice test. There are 10 questions. After the data had been analyzed, the researchers conclude that the effect of speed reading technique on the students’ ability in comprehending a text was high. It was found that the value of t-test > t-table (1, 96 > 1, 67). It means that the use of speed reading technique on the students’ ability in comprehending a text is significant effective. Based on the result, it can be seen that the students’ reading comprehension ability increases. They can understand the passages easier and efficiently. Moreover, the students are not bored in learning English since the technique used. They can get maximum result with minimum effort.